Diseño de sistema de seguridad y salud en el trabajo con protocolo de bioseguridad para el Ecoparque Canaán S.A.S. (2022)
The present document consists of proposing the Occupational Health and Safety System (SG-SST) with Biosafety Protocol in the company Ecoparque Canaán S.A.S, in accordance with the Colombian regulatory framework in the municipality of La Mesa, Cundinamarca. The development of the SG-SST is of vital importance, since it seeks compliance with the norms, requirements and procedures for employers and contractors established by law, with the objective of anticipating, identifying, evaluating and controlling the risks that may affect the safety and health of employees in the performance of their duties. The implementation of the Biosafety Protocol seeks to protect the population, for which compliance is mandatory, thus taking measures to reactivate the tourism sector, with the goal of mitigating the risk of contagion of pathological agents, in this case, SARS. -CoV-2, (Covid-19).